Perlindungan HAM Dari Perbudakan Modern Bagi ABK Indonesia di Kabupaten Tegal (Studi Pada ABK yang Tergabung Di Komunitas INFISA) - Satriya Aldi Putrazta; Caesar Dimas Edwinarta; Annas Rasid Musthafa; Nur Alifia Fitriani; Dzakirah Najyala Fakhirani El-difra (UNES Law Review, 2023)
The protection of human rights for crew of vessels, which is one of the professions in the seafaring and maritime sector, has become an urgency after the increasing cases of modern slavery in Indonesia. Therefore, this research will examine the implementation and optimization of human rights protection for Indonesian crew of vessels, especially those from Tegal Regency. This research uses an empirical legal research method using a descriptive qualitative approach to examine the problems and strategies for optimizing human rights protection for Indonesian crew of vessels. Based on the results of this research, it explains that the practice of modern slavery that often occurs with Indonesian crew of vessels includes exploitation of workers by forcing them to work for 18 hours or more a day, inadequate work wages, a workplace atmosphere that is not conducive, and a lack of supporting facilities for the comfort and welfare of workers. In addition, there are other findings that explain that the protection of the human rights of crew of vessels is regulated in Indonesian legislation and international conventions that have obliged all levels of society to participate in providing human rights protection to Indonesian crew of vessels.